Gender-specific images of the athletes' body in workers' sport in Austria from 1945-1971 - Anne Weber (Bern Open Publishing, 2024)
The study to be presented deals with gender-specific images of the athletes' bodies in workers' sports in Austria from 1945 to 1971. High performance sports and exercise culture are increasingly becoming the focus of social and cultural-historical analyses (Stieglitz, 2018). However, less attention has been paid to the connection between bodies doing sport, their socio-cultural meanings and their visual representations (Stieglitz, 2018). In particular sports photography was largely ignored in scientific studies (O'Mahony, 2018). The present study uses sport-historical photographs to deconstruct gender-stereotyped representations of the athlete's body in the workers' sport movement in Austria from 1945 to 1971. Questions to be answered include the division of sports between men and women and which stereotypes are manifested through this gender-specific distribution, how women and women's bodies are depicted in the photographs and which gender-specific discourses are established as a result, which specific discursive attributions of femininity and athletes' female bodies are re/produced and in which media settings these images are produced, published and received. This topic is of particular interest because emancipatory motives for including female workers in the sports movement emerged particularly early in the workers sports movement. The aim was to achieve theoretical and practical equality for both genders in political, cultural and social terms, even so the natural differences between sexes were always pointed out. Nevertheless, the expansion of women's sports in Austria has been very successful (Krammer, 1987). With regard to the research material, the archive holdings of the "Verein für Geschichte der ArbeiterInnenbewegung" in Vienna are viewed and analysed. The special focus is on a private and partly published photo collection, which particularly includes around 600,000 photos from the 1950s-1980s and images from magazines and another photo collection beginning 1945. The core of the study is visual history. The aim is not only to perceive images as illustrations (Stieglitz, 2018) and to analyse their representation (Bernhardt, 2013), but also to examine them as an independent entity in historical research (Stieglitz, 2018). This not only expands the source base, but also opens up new methodological possibilities (Bleichmar & Schwartz, 2019). The focus of visual history is the whole field of visual practices of self-representation, the staging and appropriation of the world, and finally the visual mediality of experience and history (Bernhardt, 2013). In order to largely rule out misinterpretations additional methods are used. Among other things, this includes content analysis, discourse analysis and methods of reception and audience research. Discourse analysis is useful to uncover the underlying social and cultural discourses that shape the meaning and interpretation of the images. Reception and audience research can be used to determine who the main readership is and how the target group perceives and interprets the images. The study is part of a bigger doctoral thesis research project and still in an early stage, so interim results will be presented at the congress. By means of specifically selected examples of photographic documents an insight into the relatively new field of visual history will be provided. References Berhardt, M. (2013). Visual history. Zeitschrift für Geschichtsdidaktik, 12(1), 5-8. https://doi-org.uaccess.univie.ac.at/10.13109/zfgd.2013.12.1.5 Bleichmar, D., & Schwartz, V. (2019). Visual history: The past in pictures. Representations, 145(145), 1-31. https://doi.org/10.1525/rep.2019.145.1.1 Krammer, R. (1987). Der ASKÖ und die Wiener Arbeiterolympiade 1931 [The ASKÖ and the 1931 Vienna Labour Olympics]. In H. J. Teichler & G. Hauck (Eds.), Illustrierte Geschichte des Arbeitersports (180-185). Dietz. O'Mahony, M. (2018). Through a glass darkly: Reflections on photography and the visual representation of sport. Historical Social Research, 43(2), 25-38. https://doi.org/10.12759/hsr.43.2018.2.25-38 Stieglitz, O. (2018). Der Reiz der Bilder. Sportgeschichte als visuelle Körpergeschichte [The allure of images. Sports history as a visual history of the body]. In M. Marschik, A. Meisinger, R. Müllner, J. Skocek, & G. Spitaler (Eds.), Images des Sports in Österreich: Innensichten und Außenwahrnehmungen (1st ed., pp. 21-32). V&R Unipress.